Boundary conditions and the Dirac spinor - Alonso, Vidal; De Vincenzo, Salvatore; Mondino, Luigi (Ciencia)
A relativistic “free” particle in a one-dimensional box is studied. The impossibility of the wavefunction vanishing completely at the walls of the box is proven. Various physically acceptable boundary conditions that allow non-trivial solutions for this problem are proposed. The non-relativistic limits of these results are obtained.